Manajemen Pemberdayaan Masyarakat - Harahap, Masrul Efendi Umar (FDIK IAIN Padangsidimpuan, 2020)
Abstrak : This research examines the management of community empowerment with the aim to find out the stages and models of empowerment activities in the midst of the community starting from the planning, organizing, directing and controlling processes. Researchers use the literature review method by analyzing good community empowerment activities using management theories that fit the empowerment context, while the results of this study are, that empowerment activities must be carried out in accordance with good management processes, ranging from the planning process to with supervision so that the empowerment activities carried out are able to realize empowered communities. Furthermore, models in community empowerment management are, according to Jack Rothman (a) empowering local communities, (b) social planning and, (c) social action, saving writers (a) empowering education (b) health and environment and, ( c) economy. In an organization / institution there are three approaches that can be done in community empowerment activities, namely, The Welfare Approach, The Development Apporoach and Empowerment Approach.